Characteristics of Pregnant Women With Syphilis and Factors Associated With Congenital Syphilis at a Chicago Hospital. (3rd April 2022) - Thornton, Corinne; Chaisson, Lelia H; Bleasdale, Susan C
Abstract: Background: Congenital syphilis incidence has more than tripled in recent years, in parallel with the resurgence of syphilis among reproductive-aged women. An understanding of risk factors associated with maternal syphilis infection can guide prevention of congenital syphilis through prenatal diagnosis and treatment. We aimed to describe factors associated with maternal syphilis and congenital syphilis at a public medical center in Chicago, Illinois. Methods: Maternal syphilis diagnoses were identified using a database for local health department reporting. Medical records were reviewed for infant congenital syphilis diagnoses, sociodemographic information, medical history, and other behavioral factors. Maternal characteristics associated with congenital syphilis were assessed using logistic regression. Results: Of 106 maternal syphilis diagnoses between 2014 and 2018, 76 (72%) had a known pregnancy outcome; of these, 8 (11%) delivered an infant with congenital syphilis. Women with psychiatric illness and noninjection substance use each had a >5-fold increased odds of having an infant with congenital syphilis. Cases with congenital syphilis were more likely to have late or scant prenatal care and initiated treatment nearly 3 months later in pregnancy. None were human immunodeficiency virus positive or reported incarceration, intravenous substance use, sex work, or having sex with men who have sex with men. Conclusions: Maternal psychiatric illness and substance use may have complicated prenatal care and delayed syphilis treatment, describing a population in need of public health intervention. Women experiencing such barriers to care may benefit from closer follow-up after a prenatal syphilis diagnosis to prevent congenital transmission. Abstract : Understanding congenital syphilis risk factors helps identify women experiencing barriers to care. Our medical record review suggests that maternal psychiatric illness and substance use complicated prenatal care and delayed syphilis treatment, describing a population in need of public health intervention.